Green bioprinting: Fabrication of photosynthetic algae‐laden hydrogel scaffolds for biotechnological and medical applications. Issue 2 (12th February 2015) - Lode, Anja; Krujatz, Felix; Brüggemeier, Sophie; Quade, Mandy; Schütz, Kathleen; Knaack, Sven; Weber, Jost; Bley, Thomas; Gelinsky, Michael
Abstract : Embedding of mammalian cells into hydrogel scaffolds of predesigned architecture by rapid prototyping technologies has been intensively investigated with focus on tissue engineering and organ printing. The study demonstrates that such methods can be extended to cells originating from the plant kingdom. By using 3D plotting, microalgae of the species Chlamydomonas reinhardtii were embedded in 3D alginate‐based scaffolds. The algae survived the plotting process and were able to grow within the hydrogel matrix. Under illumination, the cell number increased as indicated by microscopic analyses and determination of the chlorophyll content which increased 16‐fold within 12 days of cultivation. Photosynthetic activity was evidenced by measurement of oxygen release: within the first 24 h, an oxygen production rate of 0.05 mg L −1 h −1 was detected which rapidly increased during further cultivation (0.25 mg L −1 h −1 between 24 and 48 h). Furthermore, multichannel plotting was applied to combine human cells and microalgae within one scaffold in a spatially organized manner and hence, to establish a patterned coculture system in which the algae are cultivated in close vicinity to human cells. This might encourage the development of new therapeutic concepts based on the delivery of oxygen or secondary metabolites as therapeutic agents by microalgae.